Osteoinductive Material to Fine-Tune Paracrine Crosstalk of Mesenchymal Stem Cells With Endothelial Cells and Osteoblasts - Rammal, Hassan; Entz, Laura; Dubus, Marie; Moniot, Aurélie; Bercu, Nicolae B.; Sergheraert, Johan; Gangloff, Sophie C.; Mauprivez, Cédric; Kerdjoudj, Halima (Frontiers in Bioengineering and Biotechnology, 2019)
While stem cell/biomaterial studies provide solid evidences that biomaterial intrinsic cues deeply affect cell fate, current strategies tend to neglect their effects on mesenchymal stem cell (MSCs) secretory activities and resulting cell-crosstalks. The present study aims to investigate the impact of bone-mimetic material (B-MM), with intrinsic osteoinductive property, on MSCs mediator secretions; and to explore underlying effects on cells involved in bone regeneration. Human MSCs were cultured, on B-MM, made from inorganic calcium phosphate supplemented with chitosan and hyaluronic acid biopolymers. Collected MSCs culture media were assessed for mediators release quantification and used further to stimulate endothelial cells (ECs) and alveolar bone derived osteoblasts (OBs). Without osteogenic supplements, MSCs committed into bone lineage forming thus 3D bone-like nodules after 21 days. Despite a weak percentage of cell commitment, our data elucidate new aspects of osteoinductive material effect on MSCs functions through the regulation of the secretion of mediators involved in bone regeneration and subsequently the MSCs/ECs indirect crosstalk with osteogenesis-boosting effect. Using MSCs culture media, we demonstrate a large potential of osteoinductive materials and MSCs in bone regenerative medicine. Such strategies could help to address some insights in cell-free therapies using MSCs derived media.